Proposal For a General Allocation of Special Drawing Rights. (Policy Papers; Policy Paper, 2021)
On June 25, the Executive Board discussed a proposal for a historic USD 650 billion general allocation of SDRs to address the long-term global need to supplement existing reserve assets. Following concurrence by the Executive Board on July 8, the Managing Director submitted the proposal to the Board of Governors on July 9 for its approval by August 2. If approved, which requires an 85 percent majority of the total voting power, the allocation would become effective by the end of August. The proposal makes a case for an allocation of USD 650 billion (about SDR 456 billion), based on an assessment of IMF member countries' long-term global reserve needs. It also includes measures to enhance the transparency and accountability in the reporting and use of SDRs while preserving the reserve asset characteristic of the SDR. The general allocation would help many EMDCs that are liquidity constrained smooth needed adjustment and avoid distortionary policies, while providing scope for spending on crisis response and vaccines.